Using in vitro model to assess stent‐stent interaction in patients with coronary artery compression. (28th October 2018) - Zablah, Jenny E.; Fry, Rachel; Ross, Michael; Wilson, Neil; Morgan, Gareth
Abstract : Background: Percutaneous stent implantation in the coronary artery is a potential bailout option after coronary compression during Transcatheter pulmonary valve replacement, but the structural integrity of the coronary stent in this environment is uncertain. Methods: An invitro model was constructed to represent the interaction between coronary and outflow tract stents. One AndraStent, four CP stents, one Edwards SAPIEN XT valve stent and combination of AndraStent with CP stent were incrementally compressed against a coronary stent. The stent diameters were measured with a code developed in MATLAB. The relative decrease in diameter was calculated for each stent over a range of compression. Results: In all combinations of stents, coronary stent lost significantly more relative diameter when compared with larger outflow tract stents. At maximum compressive amplitude, average percent decrease in diameters of AndraStent(r) versus coronary stent: 8.1 ± 0.8% and 36.5 ± 11.1% respectively. CP stent™ versus coronary stent, the decrease was 5.7 ± 0.8% and 45.2 ± 9.2% respectively. Combined CP stent™ mounted within the AndraStent(r), versus coronary stent: 3.9 ± 0.5% and 54.5 ± 4.2% respectively. Edwards Sapien stent versus the coronary stent: 1.7 ± 0.1% and 68.9 ± 1.1% respectively. Conclusion: The relative deformation of the coronary stent was significantly higher than deformation of the other stents. Edwards Sapien XT valve stent has greater relative radial force demonstrated by the greater relative decrease in diameter of the coronary stent at final compressive amplitude. These results support the concern that coronary stenting in the presence of coronary compression by an outflow tract stent implantation is likely to result in a significantly compromised coronary lumen.